The relationship between responsible leadership and organizational citizenship behavior in the hospitality industry - Freire, C. (2021)
The purpose of this study is to explore the mediating role of the perception of social responsibility, and organizational identification, in the relationship between responsible leadership and organizational citizenship behavior in the hospitality industry. A questionnaire was answered by 214 frontline employees of four and five-star hotels, in the north of Portugal. Results indicate that there is a mediation model, which uses the effect of the perception of social responsibility and organizational identification in the relationship between responsible leadership and organizational citizenship behaviors. This study is a first attempt to propose a parallel multiple mediator model that explores the effect of hotel frontline employees’ perceptions of the importance of social responsibility, as well as the effect of employees’ identification with the organization, both of which act as mediators in the relationship between responsible leadership and OCB in the hospitality industry.